Method for detecting oxygen content in copper / copper alloy
By using a mixed solution of nitric acid, hydrofluoric acid and water for pickling, and heating it to melt in an inert atmosphere in an inert atmosphere, the problem of difficulty in efficiently detecting the low oxygen content in copper/copper alloys in the prior art is solved, and high accuracy and efficient oxygen content detection is achieved.
Patent Information
- Application Number
- CN202510053212.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art is difficult to efficiently detect the low oxygen content in copper/copper alloys, and the detection method is complex, time-consuming and low accuracy, so it cannot meet the trace analysis needs of ultra-high-purity copper and high-purity copper alloys.
The mixed solution of nitric acid, hydrofluoric acid and water is used for pickling, and combined with flux to heat to melt in an inert atmosphere, and the oxygen content in the sample is obtained by detecting the oxygen content.
It realizes the detection of oxygen content below 3ppm, with high detection accuracy, simple preparation of pickling liquid and short pickling time, meeting the detection needs of ultra-high-purity copper and high-purity copper alloys.
Smart Images

Figure BDA0005240608780000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal component analysis, and in particular to a method for detecting oxygen content in copper / copper alloy. Background Art
[0002] With the rapid development of the electronics and information industries, the requirements for the materials of sputtering alloy targets are getting higher and higher. Copper and copper alloys are widely used because of their extremely high electrical conductivity, excellent thermal conductivity, corrosion resistance, anti-electromigration ability and extremely low dielectric constant. Copper and copper alloy targets have become indispensable sputtering metal targets for the development of the display industry and the solar energy industry. However, ultra-high purity copper and high-purity copper alloys are very easy to be oxidized during the production and processing process, resulting in a high oxygen content, especially ultra-high purity semiconductor copper targets, which are very easy to be oxidized in the air, and the control of oxygen is more stringent.
[0003] On the application side of the target material, the magnetron sputtering coating process is extremely sensitive to the gases and impurities (generally in the form of oxides or hydrides) contained in the target material, because the gas elements in the target material will cause abnormal plasma discharge and the ejection of microscopic particles, affecting the sputtering rate and destroying the film structure, resulting in an increase in film defects and reduced film quality.
[0004] The national standard GB / T5121.8-2008 records a method for determining the oxygen content in copper and copper alloys. This method mixes three acids, phosphoric acid, nitric acid and glacial acetic acid, to pretreat the sample, and uses an inert gas heating and melting method to precipitate the oxygen in the sample in the form of carbon monoxide. After rare earth copper oxide, the carbon monoxide is converted into carbon dioxide, and then measured using an infrared detector. The mixed acid preparation of this method is relatively complicated, and the requirements for operators are high. The pickling time alone exceeds 10 minutes, which is time-consuming. In addition, the accuracy of the test results is low, and the detection limit is 3ppm, which cannot meet the current trace analysis of the oxygen content of ultra-high purity copper and high-purity copper alloys. Summary of the invention
[0005] The purpose of the present invention is to provide a method for detecting oxygen content in copper / copper alloy. The detection method provided by the present invention has simple pickling solution preparation, short pickling time, can detect oxygen content below 3ppm, and has high detection accuracy.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for detecting oxygen content in copper / copper alloy, comprising the following steps:
[0008] 1) pickling the copper / copper alloy sample to obtain a pickled sample; the pickling solution used in the pickling is a mixed solution of nitric acid, hydrofluoric acid and water;
[0009] 2) heating the pickled sample and flux obtained in step 1) in an inert atmosphere until they are melted, and detecting the oxygen content of the obtained gas to obtain an oxygen content test value;
[0010] 3) Subtracting the blank value from the oxygen content test value obtained in step 2) to obtain the oxygen content in the copper / copper alloy sample; the blank value testing method is: heating an equal amount of flux as in step 2) to melt under the same conditions, and testing the oxygen content of the obtained gas to obtain the blank value.
[0011] Preferably, the volume ratio of nitric acid, hydrofluoric acid and water in the pickling solution of step 1) is (2-7): (0.5-1):5.
[0012] Preferably, the pickling temperature in step 1) is 30-45° C., and the pickling time is 1-5 min.
[0013] Preferably, the pickling in step 1) is ultrasonic cleaning, and the power of the ultrasonic cleaning is 50-100W.
[0014] Preferably, the mass of the copper / copper alloy sample in step 1) is 0.2-1 g.
[0015] Preferably, the acid washing in step 1) further comprises water washing, organic solvent washing and drying in sequence.
[0016] Preferably, in step 2), the mass ratio of flux to pickled sample is (0.5-2):1.
[0017] Preferably, in step 2), the flux is pure nickel or pure tin.
[0018] Preferably, the purity of the flux in step 2) is not less than 99.9%.
[0019] Preferably, the heating and oxygen content detection in step 2) are performed in an oxygen-hydrogen analyzer; the working parameters of the oxygen-hydrogen analyzer include: degassing power 3-5 kW, analysis power 3.7-4.2 kW, and oxygen analysis integration time 30-40 s.
[0020] The invention provides a method for detecting oxygen content in copper / copper alloy, comprising the following steps: 1) pickling a copper / copper alloy sample to obtain a pickled sample; the pickling solution used in the pickling is a mixed solution of nitric acid, hydrofluoric acid and water; 2) heating the pickled sample obtained in the step 1) and a flux in an inert atmosphere until they are melted, detecting the oxygen content of the obtained gas to obtain an oxygen content test value; 3) deducting a blank value from the oxygen content test value obtained in the step 2) to obtain the oxygen content in the copper / copper alloy sample; the blank value testing method is: heating an equal amount of flux as in the step 2) under the same conditions until it is melted, detecting the oxygen content of the obtained gas to obtain the blank value. The present invention uses a mixed solution of nitric acid, hydrofluoric acid and water to clean the sample. Nitric acid can corrode and clean the sample. When there are oxides or nitrides on the sample surface that are difficult to dissolve by nitric acid, the small radius of hydrogen fluoride molecules can be used to quickly penetrate the dense metal oxide layer, react with the metal oxide, destroy and dissolve the metal oxide layer, so that the nitric acid can continue to corrode and clean the sample, and achieve etching of the sample surface, effectively clean the oxides, nitrides and other impurities on the sample surface, which is beneficial to improve the accuracy of oxygen content testing; using a flux to heat and melt the sample together can reduce the melting point of copper or copper alloy, destroy covalent bonds, and be beneficial to the release of oxygen, further improving the accuracy of detection; and using a flux to improve the stability of low oxygen content detection, and achieve detection of lower oxygen content. The results of the embodiment show that the standard sample with an oxygen content of 0.00028% is tested, and the test result is 0.00026-0.00030%, and the relative standard deviation is less than 10%; the oxygen content of semiconductor copper materials is tested, and the test result is close to the third-party test result. DETAILED DESCRIPTION
[0021] All raw materials of the present invention have no particular limitation on their sources and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0022] The present invention provides a method for detecting oxygen content in copper / copper alloy, comprising the following steps:
[0023] 1) pickling the copper / copper alloy sample to obtain a pickled sample; the pickling solution used in the pickling is a mixed solution of nitric acid, hydrofluoric acid and water;
[0024] 2) heating the pickled sample and flux obtained in step 1) in an inert atmosphere until they are melted, and detecting the oxygen content of the obtained gas to obtain an oxygen content test value;
[0025] 3) Subtracting the blank value from the oxygen content test value obtained in step 2) to obtain the oxygen content in the copper / copper alloy sample; the blank value testing method is: heating an equal amount of flux as in step 2) to melt under the same conditions, and testing the oxygen content of the obtained gas to obtain the blank value.
[0026] The present invention carries out pickling on the copper / copper alloy sample to obtain the pickled sample.
[0027] The present invention has no special requirements on the shape of the copper / copper alloy sample, and any shape of copper / copper alloy can be used for the detection method of the present invention. In an embodiment of the present invention, the copper / copper alloy sample is in block or cylindrical shape.
[0028] As an embodiment of the present invention, the preparation method of the copper / copper alloy sample is: the alloy billet is processed into a rod-shaped sample with a diameter of 1 to 5 mm and a length of 3 to 7 cm by wire cutting, and then cut to obtain a columnar sample with a length of 3 to 5 mm.
[0029] In the present invention, the mass of the copper / copper alloy sample is preferably 0.2-1.0 g, more preferably 0.4-0.6 g. The mass of the copper / copper alloy sample affects the accuracy of the test result: too little sample is likely to cause large fluctuations in the test result, while too much sample will affect the release of oxygen. The present invention limits the mass of the sample to the above range, which is conducive to improving the accuracy of the test.
[0030] In the present invention, the copper / copper alloy sample is preferably subjected to a first water wash before pickling. The first water wash is preferably ultrapure water ultrasonic cleaning, the ultrasonic cleaning time is preferably 30 to 50 seconds, and the ultrasonic cleaning power is preferably 50 to 100 W. The present invention removes dust and water-soluble impurities on the sample surface through the first water wash.
[0031] In the present invention, the pickling solution used in the pickling is a mixed solution of nitric acid, hydrofluoric acid and water.
[0032] In the present invention, the concentration of nitric acid used in the pickling solution is preferably 40-70%, more preferably 50-60%; the concentration of hydrofluoric acid used in the pickling solution is preferably 30-50%, more preferably 35-45%.
[0033] In the present invention, the volume ratio of nitric acid, hydrofluoric acid and water in the pickling solution is preferably (2-7): (0.5-1): 5. If the amount of nitric acid is too much, the reaction will be too violent, which will easily cause excessive consumption of the sample, and too much nitric acid is also dangerous; hydrofluoric acid is highly corrosive, and the higher the concentration, the more dangerous it is; if the amount of acid is too little, the cleaning time will be too long. The volume ratio of nitric acid, hydrofluoric acid and water within the above range has a good cleaning effect and cleaning efficiency.
[0034] The present invention has no particular limitation on the specific preparation method of the pickling solution, and the conventional preparation method in the art can be used.
[0035] In the present invention, the pickling temperature is preferably 30-45° C., more preferably 35-40° C. The pickling temperature affects the pickling effect. If the temperature is too high, the reaction is too violent, which easily leads to excessive consumption of the sample and volatilization and decomposition of nitric acid; if the temperature is too low, the reaction speed is too slow, which affects the cleaning efficiency.
[0036] The pickling time is preferably 1 to 5 minutes, more preferably 2 to 3 minutes. The pickling time affects the pickling effect. If the time is too short, the pickling is not thorough. If the time is too long, the sample will be over-consumed and time will be wasted.
[0037] In the present invention, the pickling is preferably ultrasonic cleaning, and the power of the ultrasonic cleaning is preferably 50 to 100 W. As an embodiment of the present invention, the ultrasonic power can be 60 to 90 W, or 70 to 80 W. The pickling parameters within the above range have a good cleaning effect.
[0038] After the acid wash is completed, the present invention preferably further comprises a second water wash, an organic solvent wash and drying performed in sequence.
[0039] In the present invention, the second water washing is preferably ultrapure water ultrasonic cleaning, the second water washing time is preferably 20 to 60 seconds, more preferably 30 to 40 seconds; the power of the ultrasonic cleaning is preferably 50 to 100 W, more preferably 70 to 80 W; the number of the second water washing is preferably 1 to 4 times. The present invention removes the acid washing solution and acid washing products remaining on the sample surface through the second water washing.
[0040] In the present invention, the organic solvent cleaning is preferably acetone ultrasonic cleaning, the organic solvent cleaning time is preferably 1 to 3 minutes, more preferably 1.5 to 2.5 minutes; the ultrasonic power is preferably 50 to 100 W, more preferably 70 to 80 W. The present invention removes water-insoluble impurities such as oil stains on the sample surface by organic solvent cleaning.
[0041] In the present invention, the drying is preferably vacuum heating drying or inert gas purging. The present invention has no particular requirements on the specific parameters of the drying, as long as the solvent on the sample surface can be completely removed. As an embodiment of the present invention, nitrogen purging can be used.
[0042] The present invention heats the pickled sample and the flux until they are melted, and detects the oxygen content of the obtained gas to obtain the oxygen content test value.
[0043] In the present invention, the flux is preferably pure nickel or pure tin. In an embodiment of the present invention, the flux is a high-purity nickel capsule or a high-purity nickel basket. The flux can lower the melting point of copper or copper alloy, destroy covalent bonds, and facilitate the release of oxygen. Moreover, the use of the flux can improve the stability of low oxygen content detection and achieve detection of lower oxygen content.
[0044] In the present invention, the purity of the flux is preferably not less than 99.9%. The higher the purity of the flux, the smaller the impact on the sample test results, which is conducive to improving the accuracy of the test. In an embodiment of the present invention, the flux is a nickel capsule with a purity of 99.99%.
[0045] In the present invention, the mass ratio of the flux to the pickled sample is preferably (0.5-2):1, more preferably 1:1. If the amount of flux is too little, it cannot fully play its role. If the amount of flux is too much, it may cause splashing during the melting process of the sample, affecting the test results. The mass ratio of the flux to the pickled sample is within the above range, which is conducive to improving the efficiency of the test and the accuracy of the results.
[0046] In the present invention, the heating and oxygen content detection are preferably performed in an oxygen-hydrogen analyzer, and the working parameters of the oxygen-hydrogen analyzer preferably include: degassing power 3-5 kW, analysis power 3.7-4.2 kW, and oxygen analysis integration time 30-40 s.
[0047] As an embodiment of the present invention, the oxygen-hydrogen analyzer may use a graphite double-layer crucible, adopt a pulse heating method, and use high-purity nitrogen or high-purity argon as a carrier gas, wherein the purity of the nitrogen is above 5N.
[0048] The obtained oxygen content test value is deducted from the blank value to obtain the oxygen content in the copper / copper alloy sample.
[0049] In the present invention, the blank value test method is: heating the flux in an amount equal to that in step 2) to melt under the same conditions, and testing the oxygen content of the obtained gas to obtain the blank value.
[0050] The present invention uses a mixed acid of nitric acid and hydrofluoric acid to clean the sample. The nitric acid can perform corrosion cleaning on the sample. When there are oxides or nitrides on the surface of the sample that are difficult to be dissolved by nitric acid, the small molecular radius of hydrogen fluoride can be used to quickly penetrate a dense metal oxide layer, react with the metal oxide, destroy and dissolve the metal oxide layer, so that the nitric acid can continue to perform corrosion cleaning on the sample, and the sample surface is etched, and impurities such as oxides and nitrides on the sample surface are effectively cleaned, which is beneficial to improving the accuracy of oxygen content testing. A flux is used to heat and melt the sample together, so as to reduce the melting point of copper or copper alloy, destroy covalent bonds, and be beneficial to the release of oxygen, thereby further improving the accuracy of detection. Moreover, the flux is used to improve the stability of low oxygen content detection, so as to achieve detection of lower oxygen content.
[0051] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0052] Example 1
[0053] A method for detecting oxygen content in copper / copper alloy, the specific steps are:
[0054] The ultra-high purity copper billet (standard sample, manufacturer: Gangyan Nano, certificate number: GSB 04-2403-1-2008) was machined to obtain a rod-shaped block sample with a size of φ3mm and a length of 5cm, and then cut to obtain an ultra-high purity copper block sample with a mass of 0.6g.
[0055] The obtained ultra-high purity copper block sample was sequentially subjected to a first water wash, an acid wash at 40° C., a second water wash, an acetone ultrasonic wash, and finally a drying treatment to obtain 0.5083 g of a sample to be tested.
[0056] The first washing step was ultrasonic cleaning in ultrapure water for 30 seconds at an ultrasonic power of 100W.
[0057] The volume ratio of nitric acid, hydrofluoric acid and water in the pickling solution is 6:0.5:5; the concentration of nitric acid is 65wt%; the concentration of hydrofluoric acid is 40wt%; the cleaning time of the mixed acid solution is 3min;
[0058] The second washing is ultrasonic cleaning in ultrapure water, the number of times is 2, each washing time is 30s, and the ultrasonic power is 100W;
[0059] The ultrasonic cleaning time in acetone was 3 min, and the ultrasonic power was 100 W;
[0060] The drying process uses high-purity nitrogen to purge and remove residual acetone.
[0061] 0.5570 g of high-purity nickel capsule flux (purity 99.99%) was placed in a graphite crucible for a blank analysis test to obtain a blank value;
[0062] 0.5083 g of the sample to be tested and 0.5570 g of a high-purity nickel capsule were placed in a graphite crucible, and then placed in an oxygen-hydrogen analyzer (Gangyan Nano OH-3000). High-purity nitrogen with a purity of more than 5N was introduced into the oxygen-hydrogen analyzer. The sample was heated at an analysis power of 4100 W for 30 seconds to melt the sample in the graphite crucible cavity to generate CO gas, which entered the infrared detection cell together with the high-purity carrier gas for detection to obtain the oxygen content in the ultra-high purity copper sample.
[0063] Example 2
[0064] A method for detecting oxygen content in copper / copper alloy, the specific steps are:
[0065] The ultra-high purity copper billet (standard sample, manufacturer: Gangyan Nano, certificate number: GSB 04-2403-1-2008) was machined to obtain a rod-shaped block sample with a size of φ3mm and a length of 5cm, and then cut to obtain an ultra-high purity copper block sample with a mass of 0.6g.
[0066] The obtained ultra-high purity copper block sample was sequentially subjected to a first water wash, an acid wash at 40° C., a second water wash, an acetone ultrasonic wash, and finally a drying treatment to obtain 0.4991 g of a sample to be tested.
[0067] The first washing step was ultrasonic cleaning in ultrapure water for 30 seconds at an ultrasonic power of 100W.
[0068] The volume ratio of nitric acid, hydrofluoric acid and water in the pickling solution is 5:0.8:5; the concentration of nitric acid is 65wt%; the concentration of hydrofluoric acid is 40wt%; the cleaning time of the mixed acid solution is 3min;
[0069] The second washing is ultrasonic cleaning in ultrapure water, the number of times is 2, each washing time is 30s, and the ultrasonic power is 100W;
[0070] The ultrasonic cleaning time in acetone was 3 min, and the ultrasonic power was 100 W;
[0071] The drying process uses high-purity nitrogen to purge and remove residual acetone.
[0072] 0.6218 g of high-purity nickel capsule flux (purity 99.99%) was placed in a graphite crucible for a blank analysis test to obtain a blank value;
[0073] 0.4991 g of the sample to be tested and 0.6218 g of a high-purity nickel capsule were placed in a graphite crucible, and then placed in an oxygen-hydrogen analyzer (Gangyan Nano OH-3000). High-purity nitrogen with a purity of more than 5N was introduced into the oxygen-hydrogen analyzer. The sample was heated at an analysis power of 4100 W for 30 seconds to melt the sample in the graphite crucible cavity to generate CO gas, which entered the infrared detection cell together with the high-purity carrier gas for detection to obtain the oxygen content in the ultra-high purity copper sample.
[0074] Example 3
[0075] A method for detecting oxygen content in copper / copper alloy, the specific steps are:
[0076] The ultra-high purity copper billet (standard sample, manufacturer: Gangyan Nano, certificate number: GSB 04-2403-1-2008) was machined to obtain a rod-shaped block sample with a size of φ3mm and a length of 5cm, and then cut to obtain an ultra-high purity copper block sample with a mass of 0.8g.
[0077] The obtained ultra-high purity copper block sample was sequentially subjected to a first water wash, an acid wash at 40° C., a second water wash, an acetone ultrasonic wash, and finally a drying treatment to obtain 0.7012 g of a sample to be tested.
[0078] The first washing step was ultrasonic cleaning in ultrapure water for 30 seconds at an ultrasonic power of 100W.
[0079] The volume ratio of nitric acid, hydrofluoric acid and water in the pickling solution is 6:0.6:5; the concentration of nitric acid is 65wt%; the concentration of hydrofluoric acid is 40wt%; the cleaning time of the mixed acid solution is 3min;
[0080] The second washing is ultrasonic cleaning in ultrapure water, the number of times is 2, each washing time is 30s, and the ultrasonic power is 100W;
[0081] The ultrasonic cleaning time in acetone was 3 min, and the ultrasonic power was 100 W;
[0082] The drying process uses high-purity nitrogen to purge and remove residual acetone.
[0083] 0.5435 g of high-purity nickel capsule flux (purity 99.99%) was placed in a graphite crucible for a blank analysis test to obtain a blank value;
[0084] 0.7012 g of the sample to be tested and 0.5435 g of a high-purity nickel capsule were placed in a graphite crucible, and then placed in an oxygen-hydrogen analyzer (Gangyan Nano OH-3000). High-purity nitrogen with a purity of more than 5N was introduced into the oxygen-hydrogen analyzer. The sample was heated at an analysis power of 4100 W for 30 seconds to melt the sample in the graphite crucible cavity to generate CO gas, which entered the infrared detection cell together with the high-purity carrier gas for detection to obtain the oxygen content in the ultra-high purity copper sample.
[0085] The implementation schemes of Examples 1 to 3 were subjected to three groups of parallel tests, and the test results are recorded in Table 1.
[0086] Table 1 Oxygen content test record table of Examples 1 to 3
[0087]
[0088] Note: U in the table indicates the allowable error range; the measured value is the value after deducting the blank value (automatically deducted by the oxygen and hydrogen analyzer).
[0089] As can be seen from Table 1, the detection method provided by the present invention detects a 2.8ppm standard sample, and the relative standard deviation is within 10%, with good repeatability; the error is less than 0.00006%, which meets the detection requirements of ultra-high purity copper or high purity copper alloy.
[0090] Example 4
[0091] A method for detecting oxygen content in copper / copper alloy, the specific steps are:
[0092] The ultra-high purity copper billet (a certain semiconductor copper material) was mechanically processed to obtain a rod-shaped block sample with a size of φ4mm and a length of 3cm, and then cut to obtain an ultra-high purity copper block sample with a mass of 0.6g.
[0093] The obtained ultra-high purity copper block sample was sequentially subjected to a first water wash, an acid wash at 40° C., a second water wash, an acetone ultrasonic wash, and finally a drying treatment to obtain 0.5156 g of a sample to be tested.
[0094] The first washing step was ultrasonic cleaning in ultrapure water for 30 seconds at an ultrasonic power of 100W.
[0095] The volume ratio of nitric acid, hydrofluoric acid and water in the pickling solution is 5:1:5; the concentration of nitric acid is 65wt%; the concentration of hydrofluoric acid is 40wt%; the cleaning time of the mixed acid solution is 3min;
[0096] The second washing is ultrasonic cleaning in ultrapure water, the number of times is 2, each washing time is 30s, and the ultrasonic power is 100W;
[0097] The ultrasonic cleaning time in acetone was 3 min, and the ultrasonic power was 100 W;
[0098] The drying process uses high-purity nitrogen to purge and remove residual acetone.
[0099] 0.5835 g of high-purity nickel capsule flux (purity 99.99%) was placed in a graphite crucible for a blank analysis test to obtain a blank value;
[0100] 0.5156 g of the sample to be tested and 0.5835 g of a high-purity nickel capsule were placed in a graphite crucible, and then placed in an oxygen-hydrogen analyzer. High-purity nitrogen with a purity of more than 5N was introduced into the oxygen-hydrogen analyzer. The sample was heated at an analysis power of 4200 W for 30 seconds to melt the sample in the graphite crucible cavity to generate CO gas, which entered the infrared detection cell together with the high-purity carrier gas for detection to obtain the oxygen content in the ultra-high purity copper sample.
[0101] Comparative Example 1
[0102] The raw materials and the detection method are the same as those in Example 4, except that the pickling solution used in the pickling is the mixed acid solution in the national standard GB / T5121.8-2008.
[0103] Comparative Example 2
[0104] The raw materials and detection method are the same as those in Example 4, except that no flux is added during heating.
[0105] The samples used in Example 4 and Comparative Examples 1-2 were sent to a third-party testing agency (Bofeik), and the test results are recorded in Table 2.
[0106] Table 2 Oxygen content test record table of Example 4 and Comparative Examples 1-2
[0107] Third-party test results (ppm) Test results (ppm) Error(ppm) Example 4 1 0.8 0.2 Comparative Example 1 1 2.2 1.2 Comparative Example 2 1 0.5 0.5
[0108] As can be seen from Table 2, in Comparative Example 1, the national standard pickling solution was used, and the same pickling temperature and time as the technical solution of the present invention were used. The impurities on the surface of the sample could not be completely removed, and the detection accuracy was poor. In Comparative Example 2, no flux was used, the sample melting was unstable, and the oxygen in the sample was not completely released, resulting in a large error in the result.
[0109] It can be seen from the above embodiments and comparative examples that the detection method provided by the present invention has good repeatability and small error in the detection results, which meets the detection requirements of ultra-high purity copper or high-purity copper alloys; and the sample can be thoroughly pickled in a shorter time, thereby improving the detection accuracy; by using a flux, the oxygen in the sample can be released more thoroughly, thereby improving the accuracy of the detection.
[0110] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for detecting oxygen content in copper / copper alloy, characterized in that: The following steps are involved: 1) pickling the copper / copper alloy sample to obtain a pickled sample; the pickling solution used in the pickling is a mixed solution of nitric acid, hydrofluoric acid and water; 2) heating the pickled sample and flux obtained in step 1) in an inert atmosphere until they are melted, and detecting the oxygen content of the obtained gas to obtain an oxygen content test value; 3) Subtracting the blank value from the oxygen content test value obtained in step 2) to obtain the oxygen content in the copper / copper alloy sample; the blank value testing method is: heating an equal amount of flux as in step 2) to melt under the same conditions, and testing the oxygen content of the obtained gas to obtain the blank value.
2. The detection method according to claim 1, characterized in that: The volume ratio of nitric acid, hydrofluoric acid and water in the pickling solution of step 1) is (2-7): (0.5-1):
5.
3. The detection method according to claim 1 or 2, characterized in that: The pickling temperature in step 1) is 30-45° C., and the pickling time is 1-5 minutes.
4. The detection method according to claim 3, characterized in that: The pickling in step 1) is ultrasonic cleaning, and the power of the ultrasonic cleaning is 50-100W.
5. The detection method according to claim 1, characterized in that: In the step 2), the mass ratio of flux to pickled sample is (0.5-2):
1.
6. The detection method according to claim 1 or 5, characterized in that: In the step 2), the flux is pure nickel or pure tin.
7. The detection method according to claim 6, characterized in that: The purity of the flux in step 2) is not less than 99.9%.
8. The detection method according to claim 1, characterized in that: The mass of the copper / copper alloy sample in step 1) is 0.2-1 g.
9. The detection method according to claim 1, characterized in that: After the acid washing in step 1), the process further includes washing with water, washing with an organic solvent and drying.
10. The detection method according to claim 1, characterized in that: The heating and oxygen content detection in step 2) are performed in an oxygen-hydrogen analyzer; the working parameters of the oxygen-hydrogen analyzer include: degassing power 3-5 kW, analysis power 3.7-4.2 kW, and oxygen analysis integration time 30-40 s.
Citation Information
Cited By
Combined detection method and system for oxygen content of oxygen-free copper
CN120992297A
Detection method for detecting content of oxygen and nitrogen in aluminum-chromium alloy
CN121805308A